Intratumoral microbiota: synergistic reshaping of lung cancer microenvironment via inflammation and immunity - Zhang, Ruilin; Li, Zhao; Liu, Xingfei; Qiu, Zhengzhou; Li, Yongxuan; Gao, Chenggen; Guo, Changying (Frontiers in Immunology, 2026)
As high-throughput sequencing tools have advanced in recent years, scientists have discovered that lung cancer tissues are not sterile. The intratumoral microbiota exists in the tumor parenchyma and stroma in a low-biomass form. This finding has overturned the traditional concept of “sterile tumors” and brought the intratumoral microbiota to the forefront of tumor research. In this review, we focus on elucidating the mechanisms by which intratumoral microbiota influence lung cancer cells and the tumor microenvironment (TME), with the aim of clarifying their role in lung cancer progression. The intratumoral microbiota does not exist as a passive resident. Instead, it may actively induce and maintain a chronic inflammatory state through the secretion of metabolites, activation of signaling pathways, immune suppressor cell recruitment, and upregulation of immune checkpoint molecule expression, thereby promoting tumor cell proliferation, invasion, and immune evasion. From a clinical translation perspective, we explore the potential of using intratumoral microbiota characteristics to predict immunotherapy efficacy. Additionally, we assess the application prospects of engineered bacteria and targeted nanobiotics, which are based on synthetic biology, in reshaping the immune microenvironment. However, the field still faces significant challenges, particularly as the low biomass nature of lung tissues makes sequencing data highly susceptible to reagent contamination and batch effects. Additionally, the synergistic role of non-bacterial components such as fungi and viruses in the tumor ecosystem is often overlooked. Future research needs to establish rigorous quality control standards and integrate multi-omics technologies to comprehensively analyze the dynamic interaction network between the microbiota and host immunity, which will drive the clinical implementation of microbiome-based precision diagnostic and therapeutic strategies for lung cancer.